2012
DOI: 10.3892/mco.2012.36
|View full text |Cite
|
Sign up to set email alerts
|

Deguelin, a novel anti-tumorigenic agent targeting apoptosis, cell cycle arrest and anti-angiogenesis for cancer chemoprevention

Abstract: Deguelin is a natural compound of the flavonoid family products isolated from Lour. or (Leguminosae). It exhibited significant anti-tumorigenesis and anti-proliferative activity in various types of cancer both and. Deguelin induced cell apoptosis by blocking anti-apoptotic pathways, such as PI3K-Akt, IKK-IκBα-NF-κB and AMPK-mTOR-survivin, while inhibiting tumor cell propagation and malignant transformation through p27-cyclinE-pRb-E2F1 cell cycle control and HIF-1α-VEGF anti-angiogenic pathways. In pre-clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…Consistently, a recent study showed that deguelin could inhibit cancer cells growth with apoptosis being involved [17,25,26]. Furthermore, we found that deguelin promotes accumulation of autophagosomes.…”
Section: Discussionsupporting
confidence: 90%
“…Consistently, a recent study showed that deguelin could inhibit cancer cells growth with apoptosis being involved [17,25,26]. Furthermore, we found that deguelin promotes accumulation of autophagosomes.…”
Section: Discussionsupporting
confidence: 90%
“…Although the suppression of multiple protein kinases, transcription factors and signal transduction pathways are involved in deguelin-mediated anti-tumor activities, the underlying mechanisms of how deguelin utilizes the tumor suppression effect through the metabolic pathways, were not fully understood [30]. Here, for the first time, we demonstrated that along with the down-regulation of HK2, the glycolysis in NSCLC was significantly inhibited after deguelin treatment.…”
Section: Discussionmentioning
confidence: 87%
“…deguelin (Figure 2F) and (−)-epigallocatechin-3-gallate (ECGT) (Figure 2G). Deguelin is a rotenoid molecule initially isolated from the African plant Mundulea sericea (Leguminosae) and later from other plants, which displayed potent and selective apoptotic and antiangiogenic effects on a variety of cancer cells (lung, prostate, gastric, and breast cancer) [122]. ECGT is the major polyphenol extracted from green tea, widely investigated for its antioxidant properties and for its possible effects in cancer prevention [123].…”
Section: Atra/arsenic Oxide Deguelin and (−)-Epigallocatechin-3-gallatementioning
confidence: 99%